Mitsubishi Electric / Wan Ahmad Mubin Pahimi - Pahimi, Wan Ahmad Mubin (2022)
The purpose of the project is to figure out what the product's problem is. Mitsubishi Electrics is the company I've picked for my research, and among their many home appliance products, I've chosen the Mitsubishi Electric Refrigerator 710l 4-Door Inverter 5-Star Energy Saving MR-L78EN. In this case study, I used a SWOT analysis to determine the MR-L78EN Refrigerator's strengths, weaknesses, opportunities, and threats. The primary issue I found with this MR-L78EN Refrigerator is that it is believed to be pricey in Malaysia, and it lacks an official online shop, unlike other brands like Hitachi and Sharp. From the problem, I have come up with the best possible solution which is to establish an official online store in the Malaysian market.